Expected effective retirement age and exit age in the Nordic countries and Estonia - Kannisto, Jari; Vidlund, Mika (Finnish Centre for Pensions, 2022)
This report examines the effective retirement age in the Nordic countries and Estonia by using two complementary indicators: the expected effective retirement age (expectancy) and the labour market exit age (exit age). Since the exit age and the expectancy are closely related, they tell us mainly the same story. In all the countries studied, policy measures have sought to delay retirement. Indicators show that this has also happened. Although there are still some clear differences between countries within these indicators, they have narrowed during the review period.